Penerapan Pendekatan Teaching at the Right Level (TARL) untuk Meningkatkan Hasil Belajar Mata Pelajaran Matematika Materi Pokok Operasi Penjumlahan dan Pengurangan pada Siswa Kelas IV Di SDN 50 Cakranegara - Pratiwi, Dian Galuh; Husniati, Husniati; Kaninta, Novianti (Mataram University, 2025)
This study aims to analyze the implementation of the Teaching at the Right Level (TaRL) approach in improving students’ learning outcomes on the topic of addition and subtraction operations in fourth-grade students at SDN 50 Cakranegara. The method used in this research was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The population in this study comprised all fourth-grade students at SDN 50 Cakranegara, from which a sample of 28 students was selected based on initial assessment results. The sampling technique used was purposive sampling, where students were chosen based on specific criteria—namely, fourth-grade students at SDN 50 Cakranegara with diverse basic mathematical abilities. The results showed a significant improvement in students’ learning outcomes, as indicated by the increase in average scores from Cycle I to Cycle II. In Cycle I, the average student score reached 70, while in Cycle II, it increased to 80. Furthermore, the percentage of students achieving mastery learning rose from 64% in Cycle I to 93% in Cycle II. The study concludes that the implementation of the TaRL approach is effective in improving students’ mathematics learning outcomes, particularly in addition and subtraction operations, and can serve as an alternative instructional method that is more responsive to students’ learning needs.